Paradoxical Reaction in Tuberculous Meningitis and Tuberculoma: Diagnostic Challenges Following Incomplete Treatment - Situmeang, Rocksy Fransisca V; Gabriella, Nadia (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Exacerbation of clinical or radiological findings in tuberculous meningitis (TBM) may result from a paradoxical reaction (PR), an immune-mediated response occurring in 6–30% of cases during or after anti-tuberculosis treatment (ATT). This case highlights the potential for PR to occur in the context of an incomplete ATT regimen. Case Illustration: A 20-year-old female presented with a 1-month history of headache, fever, double vision, nuchal rigidity, and bilateral abducens palsy. Cerebrospinal fluid analysis revealed pleocytosis and elevated protein, while brain MRI demonstrated leptomeningeal enhancement with multiple tuberculomas. She received standard ATT (RHZE), but discontinued therapy before completion due to symptom resolution and medication burden. One year later, she developed altered sensorium and behavioral changes; MRI showed new tuberculomas with edema despite negative serology. A diagnosis of PR was made, and high-dose intravenous corticosteroids were administered, resulting in clinical and radiological improvement. Discussion: PR remains a diagnostic challenge, often mistaken for microbiological relapse, drug resistance, or treatment failure. It arises from a distinct immune response to mycobacterial antigens, distinguishing it from relapse or drug resistance. Conclusion: Clinicians should suspect PR in worsening TBM cases, even in the setting of incomplete ATT, to prevent misdiagnosis and initiate prompt treatment.